Purification, biochemical characterization and gene sequencing of a thermostable raw starch digesting alpha-amylase from Geobacillus thermoleovorans subsp stromboliensis subsp nov. - KASAVİ, CEYDA; TOKSOY ÖNER, EBRU (SPRINGER, 2011)
This study reports the purification and biochemical characterization of a raw starch-digesting alpha-amylase from Geobacillus thermoleovorans subsp. stromboliensis subsp. nov. (strain Pizzo(T)). The molecular weight was estimated to be 58 kDa by SDS-PAGE. The enzyme was highly active over a wide range of pH from 4.0-10.0. The optimum temperature of the enzyme was 70A degrees C. It showed extreme thermostability in the presence of Ca2+, retaining 50% of its initial activity after 90 h at 70A degrees C. The enzyme efficiently hydrolyzed 20% (w/v) of raw starches, concentration normally used in starch industries. The alpha-amylase showed an high stability in presence of many organic solvents. In particular the residual activity was of 73% in presence of 15% (v/v) ethyl alcohol, which corresponds to ethanol yield in yeast fermentation process. By analyzing its complete amyA gene sequence (1,542 bp), the enzyme was proposed to be a new alpha-amylase.
Keywords: Alpha-amylase; amyA gene sequence; Geobacillus thermoleovorans subsp stromboliensis; Raw-starch-digestion; Thermostability; BACILLUS; HYDROLYSIS; QUANTITIES; PROTEINS